The Fascist elites, government and the Grand Council - Adinolfi, G. (Portuguese Journal of Social Science, 2009)
The aim of this article is to analyse the composition of the Italian political elite during the 21-year Fascist regime (192243). Even today the writings on this subject, which have always been circumscribed by the axioms state/party (Gentile 2002; Aquarone 1995) and authoritarianism/totalitarianism (Collotti 2004; Gentile 2002; Tarchi 2003), have not managed to find a synthesis to define the regime's true nature. It is our belief that an empirical study of the political elite can help to define these questions.